Sundanese Dialect in Panjalin Village, Sumberjaya District, Majalengka Regency - Mega Sri Rahmah; Ratnawati (STKIP Muhammadiyah Kuningan, 2023)
The rapid development of technology greatly influenced the development of language, the rampant use of slank language variations caused the Sundanese dialect to be increasingly displaced and prone to extinction so the inventory of a language was greatly encouraged. In this study, the method used was descriptive qualitative. Books, and journals, are secondary sources used, and informants as primary sources. The results of this study stated that as many as 28 verbs, 32 nouns, 21 adjectives, and 3 prepositions of the Panjalin dialect, and of the 77 words only 62 words have meanings in the dictionary while the others have been mixed with languages other than Sundanese so it can be concluded that about 67.78% of the words are contained in dictionaries and about 32.22% are Sundanese dialects of Panjalin.